“Análisis de la calidad de energía en la línea de producción tetra pack, perteneciente a la planta borama, cantón La Maná, 2023.”. Propuesta de instalación de ups para la reducción de cortes de energía.” - Albarrasín Reinoso, David Fernando (2023)
The purpose of this study is to analyze the power quality in the Tetra Pack production line of the Borama Plant in the Canton of La Maná in 2023, with the objective of identifying and addressing problems related to power outages that affect efficiency and production. . . To address this problem, a methodology was used that included the collection of power quality data over a specific period, the evaluation of power outages and the proposal for the installation of Uninterruptible Power Supply Systems (UPS) as a measure of mitigation. Overall results revealed that power quality on the Tetra Pack production line was poor, with frequent outages affecting operability. The proposed UPS installation was proposed as an effective solution to reduce power outages and ensure continuous power supply, thereby improving efficiency and production at the plant. This study lays the foundation for the implementation of corrective measures that will optimize energy quality in the production line, strengthening the competitiveness of the Borama Plant in the market.